Productivity and Nutrient Reaction of Maize Hybrids - El Hallof, Nóra; Sárvári, Mihály (Acta Agraria Debreceniensis, 2005)
Several factors influence the quantity and stability of maize yield, the most important being the nutrient supply, the hybrid and precipitation. In 2004, during the maize growing season the precipitation was more than the 30 year’s average, with 68.3 mm, but the distribution was unfavorable. The experiment was carried out in Debrecen at the Experimental Station of the University of Debrecen Centre of Agricultural Sciences, Department of Crop Production and Applied Ecology. We tested 10 various hybrids with their own genetic characteristics for five different fertilizer doses, in addition to the parcels without fertilization.The favorable results reached were due to the rainy season. The average yield varied between 7.78-9.67 tha-1. The DK 440, PR37M34, PR38A24, PR39D81 and PR36R10 of the hybrids reacted to higher fertilizer doses with significant growth yields, the yield (more than 11 tha-1) was the highest for N200, P125, K150 fertilizing. The other hybrids, DKC 5211, Mv Vilma and MV Maraton, gave similar results at the N120+PK fertilizer dose and the ensuing doses depressed the yield. Fertilization was more effective thanks to the precipitation. The fourth and fifth dose increased or decreased maize yield depending on the nutrient reaction of the hybrid. The agro-ecological optimum of NPK fertilization was N120, P75, K90 kgha-1.During the experiment we tested the moisture loss of five hybrids. The rainy crop year’s effect on the seed moisture content at harvest was higher than in previous years. The seed moisture content hybrids at harvest which have shorter crop years (FAO 300) was 18-19%, and hybrids with longer vegetation periods had more than 20% seed moisture content. DK 440 hybrid had the intensive moisture loss of the five hybrids, at the start of the measurement, the seed moisture content was higher than 40%, and it decreased to 18.6% by harvesting.